2022
DOI: 10.1021/acs.est.2c03330
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Manganese Levels and Risk of Gestational Diabetes Mellitus: A Prospective Cohort Study

Abstract: Manganese (Mn) intake has been found to be linked with risk of type 2 diabetes. However, the role of Mn in the development of gestational diabetes mellitus (GDM) remains to be investigated. This prospective study included pregnant women from the Tongji Maternal and Child Health Cohort. A total of 2327 participants with plasma specimens before 20 weeks were included. Among the pregnant women, 9.7% (225/2327) were diagnosed with GDM. After adjustment, pregnant women with the third and highest quartile of plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 41 publications
(79 reference statements)
0
9
0
Order By: Relevance
“…Most relevant studies have focused on a single metal or a mixture of metals including up to seven species. ,, Significant associations with GDM have been reported for Cu, Mn, Al, As, V, Cd, and Fe in single-metal exposure studies, 18 – 24 although other studies reported otherwise. For example, Li et al reported a significant and positive correlation between plasma Mn and GDM risk in a prospective study, but the trend was not observed in another study with or without adjusting for confounding factors . While sociodemographic characteristics or sample size could vary largely between studies and thus complicate the association analysis, one thing important to the outcome is that concurrent exposure to the metal mixture could produce different effects from what can be expected from single-metal exposure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most relevant studies have focused on a single metal or a mixture of metals including up to seven species. ,, Significant associations with GDM have been reported for Cu, Mn, Al, As, V, Cd, and Fe in single-metal exposure studies, 18 – 24 although other studies reported otherwise. For example, Li et al reported a significant and positive correlation between plasma Mn and GDM risk in a prospective study, but the trend was not observed in another study with or without adjusting for confounding factors . While sociodemographic characteristics or sample size could vary largely between studies and thus complicate the association analysis, one thing important to the outcome is that concurrent exposure to the metal mixture could produce different effects from what can be expected from single-metal exposure.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to Cu and Ga, other metals, including Mn, Fe, Ni, Rb, Sr, Pb, Co, and V, also exhibited significant associations with GDM in the single-exposure analysis, although they exhibited a much lower relative importance in the mixture effect. Epidemiological studies have reported the associations of single exposure to these metals with GDM or T2D. ,,, Toxicological investigations also reported that selected metals (e.g., Mn, Ni, Pb, and Co) could disrupt glucose uptake and alter related molecular mechanisms involved in glucose metabolism and homeostasis regulations. Therefore, gestational exposure to such a complexity of metals collectively elevated the GDM risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of GDM exceeds 20% in regions such as Asia and South America, and this rate continues to increase. 1 In China, the current status of GDM is confronting significant challenges driven by economic development and the implementation of the national "multichild" policy. 2,3 Pregnant women diagnosed with GDM are at an elevated risk of experiencing postpartum hemorrhage, premature rupture of membranes, gestational hypertension, and type 2 diabetes (T2D).…”
Section: Introductionmentioning
confidence: 99%
“…Gestational diabetes mellitus (GDM) is a distinct type of diabetes that occurs during pregnancy, and its effects extend far beyond the pregnancy period. The prevalence of GDM exceeds 20% in regions such as Asia and South America, and this rate continues to increase . In China, the current status of GDM is confronting significant challenges driven by economic development and the implementation of the national “multichild” policy. , Pregnant women diagnosed with GDM are at an elevated risk of experiencing postpartum hemorrhage, premature rupture of membranes, gestational hypertension, and type 2 diabetes (T2D). More alarmingly, the offspring of GDM patients have been observed to face significantly increased risks of preterm birth, obesity, and cardiovascular diseases. , Although several conventional risk factors including older maternal age, family history of diabetes, obesity, and an unhealthy diet have been reported to be associated with GDM, the etiology of GDM remains inconclusive.…”
Section: Introductionmentioning
confidence: 99%